Mycobacterium Kansasii infection in a psoriasis patient treated with adalimumab and switch to apremilast: first report and literature review - Alexandra Maria Giovanna Brunasso; Sanja Javor; Emanuele Pontali; Simona Sola; Cesare Massone (PAGEPress Publications, 2021)
Patient under anti-TNF-alpha treatment have an increased risk of mycobacterial infections, particularly tuberculosis. Only four case reports of Mycobacterium kansasii infection under anti-TNF-α treatment (two with etanercept, two with infliximab) have been reported, but none under adalimumab. A 72-year-old man treated with adalimumab for psoriasis vulgaris and arthropathic psoriasis, complained on nocturnal cough, occasional hemoptysis and the new onset of ill-defined, reddish, asymptomatic persistent plaquesnodules covered by serum crusts on his back, on the dorsum of the right hand and right middle finger. Routine laboratory investigations, HIV and TB screening (QuantiFERONTB- Gold test) were all within normal limits. A skin biopsy was inconclusive and special stainings resulted negative for microorganisms. Only PCR identified M. kansasii. The patient stopped adalimumab and started anti-TB treatment with gradual improvement of the skin lesions. At 26 months follow-up visit no signs or symptoms of relapse of M. kansasii disease occurred.